La Administración Del Talento Humano Y Su Incidencia En La Etapa De Crecimiento Y Desarrollo De La Empresa Servicom, De La Ciudad De Babahoyo - Moncada Vargas, Diego (2015)
This research aims to present as the company evolves SERVICOM stages of growth and development in the activities of human talent management, activities running human talent working in the organization with the strategy outlined is described expects an increasing number of potential customers. Human Resources is very important in a company with a trained, motivated, knowing their roles in performing daily activities, the company progressed in their activities. If the company has an organized organizational structure with organizational departments reflect existing staff know which department belongs. This is why it is very important that the company has fixed the horizon where it wants to go...